2017
DOI: 10.1080/09500693.2016.1276641
|View full text |Cite
|
Sign up to set email alerts
|

Using doubly latent multilevel analysis to elucidate relationships between science teachers’ professional knowledge and students’ performance

Abstract: Teachers make a difference for the outcome of their students in science classrooms. One focus in this context lies on teachers' professional knowledge. We describe this knowledge according to three domains, namely (1) content knowledge (CK), (2) pedagogical content knowledge (PCK), and (3) curricular knowledge (CuK). We hypothesise a positive relationship between these three domains and students' performance in science. Students' science performance was conceptualised by system thinking performance in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 73 publications
0
37
0
6
Order By: Relevance
“…A further explanation could be that CK alone does not suffice to be successful during teaching. This is supported by studies that found no direct relationship between CK and students' achievement [104][105][106] or found that PCK is the less relevant predictor for students' achievement [74].…”
Section: How Are Ck and Pck Related To Biology Teachers' Self-efficacmentioning
confidence: 70%
“…A further explanation could be that CK alone does not suffice to be successful during teaching. This is supported by studies that found no direct relationship between CK and students' achievement [104][105][106] or found that PCK is the less relevant predictor for students' achievement [74].…”
Section: How Are Ck and Pck Related To Biology Teachers' Self-efficacmentioning
confidence: 70%
“…Professional knowledge increased in all three areas (PPK, CK, and PCK). The strong effect for PCK can be evaluated particularly positively, because a relationship between PCK and students' performance has been demonstrated [90]. The stronger effect, in comparison to PPK and CK, can likely be explained by the fact that in the seminar PPK and CK content were also taught with reference to the students' later roles as biology teachers, and the linking sessions on constructing teaching materials focused on PCK.…”
Section: Discussionmentioning
confidence: 99%
“…At last, in this study, we only focused on the effect of self-directed learning and did not incorporate teachers' support. Although teachers can be powerful for students' learning (e.g., Hattie 2009), students' performance is also likely to be influenced by teacher's professional knowledge (e.g., Mahler et al 2017;Sadler et al 2013). Our first step was to examine if EvoSketch can be effective on its own (without any teachers' support), but including teacher's support in further studies (e.g., in form of class discussions or one-by-one support) may be helpful for students' understanding of abstract threshold concepts, particularly directly after working with EvoSketch.…”
Section: Limitationsmentioning
confidence: 99%